Web-Based Information System for the Stuff Inventory at UPTD PPD South Bandung Region - Pretty Louren Gultom; Eka Putri Pratami; Edi Suharto (Jurnal E-Komtek, 2022)
The inventory of stuff must be neatly arranged. Using technology supported by an information system, it is hoped that the storage of an item can be neatly arranged. To support broad mobility, a web-based platform is essential. It can provide sufficient integrity for users. This website-based inventory information system is one way to solve problems in the UPTD PPD South Bandung Region. In its design, this system uses qualitative research methods and software development methods of Software Development Life Cycle (SDLC) as well as a system analysis design, namely Data Flow Diagrams (DFD), to determine the flow of the data. The testing was limited to program quality using Blackbox testing to test the program properly.